Effect of inoculum density, host cultivars and seed treatment on the seed and seedling rot of soybean caused by Sclerotium rolfsii - P.N. THAPLIYAL, UMA SINGH and (Indian Phytopathology, 2002)
The effect of different inoculum densities, soyabean cultivars (Bragg, PK 262, PK 308, PK 327 and PK 416) and integrated management practices on the incidence of seed and seedling rot caused by S. rolfsii [Corticium rolfsii] were investigated. Seeds inoculated with C. rolfsii had 17.5% germination with only 5% normal seedlings as compared with 77.5% germination and 70% normal seedlings in the control. The pathogenic potential increased with increasing inoculum density. Soyabean cv. PK 327 was slightly tolerant and Bragg highly susceptible to pre- and post-emergence rot. In seed treatment tests with the antagonists Trichoderma harzianum and Gliocladium virens, and the fungicides thiram, Bavistin (carbendazim) and Vitavax (carboxin + thiram), both pre- and post-emergence seedling rot were effectively managed by seed treatment with carboxin + thiram plus T. harzianum or G. virens.